2022
DOI: 10.14214/sf.10598
|View full text |Cite
|
Sign up to set email alerts
|

Forest fires have long-term effects on the composition of vascular plants and bryophytes in Scots pine forests of hemiboreal Estonia

Abstract: Since fire frequency is expected to increase globally due to climate change, it is important to understand its effects on forest ecosystems. We studied the long-term patterns in species diversity, cover and composition of vascular plants and bryophytes after forest fire and the site-related factors behind them. Research was carried out in northwestern Estonia, using a chronosequence of Scots pine ( L.) stands, located on nutrient poor sandy soils, where fires had occurred 12, 23, 38, 69, 80 and 183 years ago. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 48 publications
(81 reference statements)
1
3
0
Order By: Relevance
“…This is possibly related to the recovery time for low-severity burns. Supporting our results, previous studies have indicated the effects of fire on the richness, diversity, and composition of bryophytes and lichens in temperate and boreal zones [26,[60][61][62][63][64][65] The richness of lichen and bryophyte species is higher in the control because species belonging to the bryophyte group (e.g., Breutelia, Rhacocarpus, and Syzygiella) were exclusive in the control plots. Supporting our results, previous studies have documented that the richness of cryptogams decreases in soils degraded by fire [43,44,66].…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…This is possibly related to the recovery time for low-severity burns. Supporting our results, previous studies have indicated the effects of fire on the richness, diversity, and composition of bryophytes and lichens in temperate and boreal zones [26,[60][61][62][63][64][65] The richness of lichen and bryophyte species is higher in the control because species belonging to the bryophyte group (e.g., Breutelia, Rhacocarpus, and Syzygiella) were exclusive in the control plots. Supporting our results, previous studies have documented that the richness of cryptogams decreases in soils degraded by fire [43,44,66].…”
Section: Discussionsupporting
confidence: 89%
“…In this context, Greene et al [43] and Zabala et al [66] showed that the effect of fire on the diversity of lichens and bryophytes can be temporary; therefore, their diversity can recover with the passage of time monitoring [43,44,66]. Similarly, Orumaa et al [63] and Pharo et al [71] showed that the post-fire effect has positive consequences on the diversity and richness of terricolous cryptogams due to the increase in nutritional contents such as N, K, Ca, Mg, Fe, and Mn. Finally, Wienskoski and Santos [27] point out that the richness and diversity of terricolous cryptogams (e.g., bryophytes) are limited by the time after the fire, that is, the diversity is greater when the time after the fire increases.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations